Persistent CD8+ T cell proliferation and activation in COVID-19 adult survivors with post-acute sequelae: a longitudinal, observational cohort study of persistent symptoms and T cell markers - LaVergne, Stephanie M.; Dutt, Taru S.; McFann, Kim; Baxter, Bridget A.; Webb, Tracy L.; Berry, Kailey; Tipton, Maddy; Stromberg, Sophia; Sullivan, Brian M.; Dunn, Julie; Henao-Tamayo, Marcela; Ryan, Elizabeth P. (Frontiers in Immunology, 2024)
Post-acute sequelae of COVID-19 affects the quality of life of many COVID-19 survivors, yet the etiology of post-acute sequelae of COVID-19 remains unknown. We aimed to determine if persistent inflammation and ongoing T cell activation during convalescence was a contributing factor to the pathogenesis of post-acute sequelae of COVID-19. We evaluated 67 individuals diagnosed with COVID-19 by nasopharyngeal polymerase chain reaction for persistent symptoms during convalescence at separate time points occurring up to 180 days post diagnosis. Fifty-two of these individuals were evaluated longitudinally. We obtained whole blood samples at each study visit, isolated peripheral blood mononuclear cells, and stained for multiple T cell activation markers for flow cytometry analysis. The activation states of participants' CD4 + and CD8 + T-cells were next analyzed for each of the persistent symptoms. Overall, we found that participants with persistent symptoms had significantly higher levels of inflammation at multiple timepoints during convalescence when compared to those who fully recovered from COVID-19.Participants with persistent dyspnea, forgetfulness, confusion, and chest pain had significantly higher levels of proliferating effector T-cells (CD8 + Ki67 + ), and those with chest pain, joint pain, difficulty concentrating, and forgetfulness had higher levels of regulatory T-cells (CD4 + CD25 + ). Additionally, those with dyspnea had significantly higher levels of CD8 + CD38 + , CD8 + Granzyme B + , and CD8 + IL10 + cells. A retrospective comparison of acute phase inflammatory markers in adults with and without post-acute sequelae of COVID-19 showed that CD8 + Ki67 + cells were significantly higher at the time of acute illness (up to 14 days post diagnosis) in those who developed persistent dyspnea. These findings suggest continued CD8 + T-cell activation following SARS-CoV-2 infection in adults experiencing post-acute sequelae of COVID-19, and that the increase in T regulatory cells for a subset of these patients represents the ongoing attempt by the host to reduce inflammation.